Anti-inflammatory Effects of Gallotannin in Combination With Lactobacillus plantarum in a DSS-Induced Colitis Mouse Model. (14th June 2022) - Kim, Hyemee; Wang, Qunzhe; Im, Yuri; Yan, Jing; Kim, Dahee; Kang, Jeong Hyun
Abstract: Objectives: To establish the synergistic effects of the pre/probiotics on intestinal inflammation and to elucidate the underlying mechanisms, we investigated the anti-inflammatory effects of Gallotannin (TA) and Lactobacillus plantarum (LP) in LPS-treated cells and DSS-treated mice. We hypothesized that simultaneous intake of TA and LP may modulate the intestinal microbiota and increase the conversion rate of TA into its metabolites, which have potent anti-inflammatory properties due to their regulation of the AMPK/mTOR axis in colitis. Methods: Mice were given two cycles of DSS (2.5% for 7 days) to induce chronic colitis with oral gavage of gallotannin (0.8 mg/mouse) every other day for 4 weeks. At the end of each DSS cycle, L. plantarum (10 8 CFU/100 μL; OD600 = 0.6) was fed for 3 days. Body weight, colon length, and histopathological assessment were all assessed on the final day, and blood, feces, and colon samples were taken. Results: In LPS-treated macrophage RAW 264.7, TA metabolized by LP significantly decreased the levels of IL-6 and TNF-α. In an experimental murine model of UC, we found that the combination of LP and TA improved weight gain, gut length, enlarged spleen, and histological scores while lowering the levels of TNF-α, lipocalin-2, MPO, IFN-γ, IL-17, and IL-6 in DSS-treated mice. Furthermore, colonic mRNA expression levels of Pik3r1, Akt1, and mTor were reduced in the groups that received both LP and TA. The expression of Prkaa1 (AMPKa1) and Map1lc3a (LC3) mRNA increased considerably after the co-administration of LP and TA, compared to the DSS control group. Additionally, LP and TA decreased the ratio of p-mTOR/mTOR protein expression while increasing the p-AMPK/AMPK ratio in DSS-treated mice. Mouse feces were used to measure compositional changes in the gut microbiota. Compared to the DSS control, the combination of LP and TA increased the levels of probiotics, such as Lactobacillus spp ., Lactobacillus reuteri, and Lactococcus lactis in DSS-treated mice. Conclusions: Simultaneous intake of LP and TA showed a synergistic effect in attenuating mucosal damage and decreasing inflammatory cytokines by modulating the AMPK/mTOR axis and restoring intestinal microbiota imbalance. Funding Sources: National Research Foundation of Korea (NRF) grant funded by the Korean government (MSIT) (No. 2020R1G1A1099851) and Pusan National University Research Grant, 2020.